Plant material of loquat in Asian countries - Lin S. (First international symposium on loquat, 2003)
This paper discusses which species are in the genus Eriobotrya and which plant material from loquat species are in Asian countries, especially in China, Japan and India.
1. International Symposium on Loquat, 2002/04/11-13, Valencia (Spain)